Social Housing in Urban Regeneration. Regeneration Heritage Existing Building: Methods and Strategies - Giannino, Maria Antonia; Orabona, Ferdinando (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The theme of urban regeneration has played a strategic role during the last two decades in European and national urban building policies. Current addresses, also defined in Leipzig Charter on Sustainable European Cities in 2007, indentify the necessity to invest in requalification of degraded residential assets and not in new developments, individuating in urban regeneration the main tool for development of contemporary city. Public neighborhoods have developed, historically, a wide set of common problems. They are not only due to wrong planning but also to the concept of “housing for masses”.  The original ambition of modern settlment, developed from GermanSiedlung, was to be an autonomous part, on the point of view of morphology, in urban expansion. Joined by new developments, a lot of neighborhoods became benchmarks for suburban areas and now we can define themas “new urban centralities”. So theirrole in urbandynamics has changed and they can be individuate dasprecious reserves of public spaces and potential incubators for regeneration of larger areas. Analyzing some Italian and European case studies, themostinnovative relate to the densification of open spaces, inserting new services in a general redesign of green areas; concentration of built surfaces, in order to reduce land consumption and introduction of different residential types in order to improve mischbebauung. The reasons for an active recovery are motivated by the criteria of environmental sustainability and saving land, have relaunched compact projects with medium to highdensity.